The Business Plan of Beauty Brand XYZ: Moisturizer Product - Farzanah, Nazifa; Rahmani Qastharin, Annisa (Journal of Consumer Studies and Applied Marketing, 2023)
There is rapid growth in Indonesia’s beauty industry—the desire to be physically attractive influences many Indonesians to consume skincare products. Shifting shopping behaviors from offline to online are also developed due to COVID-19. Data shows that the beauty & care category has the largest market share in the FMCG category, and there is fierce competition. XYZ brand wants to take advantage of this situation by creating effective strategies. The purpose of this research is to create a business plan that can be applied by XYZ brand, so they have relevant plans and strategies to compete. This business plan is conducted by conducting company and market analysis, including external, internal and competitive, using primary and secondary data. It shows that XYZ brand has a strong position in product quality, value, and branding but still lags behind competitors in product diversification, market share and presence. XYZ brand will develop a new moisturizer product as diversification. Digital and offline channels will be used with 14 marketing tools to market and distribute the product. The moisturizer needs 3 months of preparation and will involve several vendors. This business plan needs Rp1.058.750.000 as the initial capital and is estimated to gain Rp8.969.268.000 in revenue with a net profit of 26.42% from July 2023 - May 2024. The payback period is estimated to be around 8.015 months, ROI is 2.24. The limitation is regarding the business identity that has already been set by XYZ brand, also limitation from historical and competitor’s data. The previous business plan of XYZ brand is irrelevant to the current condition because they have strengthened their business identity, which is only covered in this business plan. This research also focuses on current market conditions and strategies to survive the fierce competition.